Oral anticoagulation therapy: current challenges in Indian scenario - Menon, Ajit; Thomas, Joy; Ichaporia, N. R.; Sahoo, Prasant Kumar; Unni, T. Govindan (International Journal of Advances in Medicine, 2020)
Over the past decade, the burden of thromboembolic diseases has increased in India; however, there is a huge gap between the diagnosis and treatment of these ailments. This is further complicated by the presence of various options for anticoagulation therapy and the absence of a clinical consensus on the use of these anticoagulants. To address this issue and establish consensus statements on the use of anticoagulation therapy in Indian settings, an expert consensus was developed in alignment with the latest available evidence. A group of 38 clinical experts discussed, in detail, various case-based scenarios on stroke prevention in atrial fibrillation (AF), anticoagulation for patients with valvular heart disease, stroke, or deep-vein thrombosis. Anticoagulation management options for special populations, including patients with renal dysfunction, elderly patients, and pregnant women, were also discussed in detail. The key opinions the experts (cardiologists, cardiovascular and thoracic surgeons, consulting physicians, and neurologists) are intended to address gaps in Indian clinical practice concerning anticoagulation therapy. Based on scientific evidence, clinical experience, and guidelines on the use of anticoagulation therapy, various consensus statements were proposed. This document was drafted, reviewed, validated, and modiﬁed by the expert panel until a ﬁnal agreement was reached. This pioneering consensus document will lay the foundation for future anticoagulation education modules based on evidence-based treatment approaches for Indian clinicians.